Clinico-bacteriological profile of spontaneous bacterial peritonitis in cirrhosis of liver with ascites - Goel, Shewtank; Pandey, Pooja Tripathi; Kumar, Abhay; Kumar, Nidhish; Arora, Deval Kumar; Singh, Abhishek (International Journal of Research in Medical Sciences, 2019)
Background: A good and an effective empirical treatment of SBP is not possible unless bacteriological spectrum and their antibiogram is clear. This becomes more important in country like India due to high antibiotic resistance. Authors aim was to assess the prevalence of SBP, clinical and microbiological profile of its variants, in patients with cirrhosis seeking care at a tertiary care teaching hospital. Methods: Patients of liver cirrhosis with ascites seeking care at study subject during January- December 2018 formed the study population. Diagnosis was based on clinical examination, biochemical investigation and ultrasonography. Diagnostic abdominal paracentesis was performed on subjects within 24 hours of admission. Ascitic fluid was aspirated. It was sent for microbiological examination. Results: Prevalence of SBP was 16.12%. Out of total ten subjects with Spontaneous Bacterial Peritonitis (SBP), six subjects were of Culture Negative Neutrocytic Ascites (CNNA). Thus most common (60%), variant of Spontaneous Bacterial Peritonitis (SBP) was Culture Negative Neutrocytic Ascites (CNNA). Prevalence of Mono-microbial Non-neutrocytic Bacterascites (MNBA) and Classic-Spontaneous Bacterial Peritonitis (C-SBP) was 20%. Two subjects found positive for MNBA, Staphylococcus aureus and Acinitobacter spp. was detected in each patient. Klebseila pneumonia, Escherichia coli and Coagulase negative Staphylococcus were found in ascitic fluid culture of C-SBP. In clinical variants of SBP, 80% subject’s complaint about abdominal pain. Hepatic-encephalopathy and fever was seen in 7(70%) patients. Rebound tenderness was seen among 60%. Conclusions: Diagnostic paracentesis should be advised to all cirrhotic patients with ascites. Ascitic fluid analysis should be sent for better selection of antibiotics thus better outcome of cirrhotic patients.